ANALISIS DAYA SAING KOPI INDONESIA DI PASAR INTERNASIONAL - Abdullah Muhlis; Sulistyaningsih Sulistyaningsih (AGRIBIOS, 2023)
Coffee is a strategic plantation commodity for the Indonesian economy. The strategic value of coffee lies in the large contribution that coffee makes to state revenues, especially in the form of foreign exchange. This research is a type of quantitative research using secondary data. The purpose of this study was to determine the comparative advantages of coffee commodities, coffee export performance and international coffee trade conditions. The results of the study show that: 1) Indonesia has a comparative advantage over coffee. This is shown by the average RCA value in the 2017–2021 period which is above 1 (one) of 1.86. 2) Indonesia can seize the export market for coffee commodities or Indonesia's position will get stronger in the export market in 2017 and 2019. 3) In the 2017-2021 period, Indonesia has strong competitiveness or Indonesia tends to be an exporting country of coffee commodities because the average -the average positive ISP score is 0.879 and Indonesia is in the export stage.